Evaluation of In vitro Anti-Cancer Activity of Methanolic Leaf Extract of Phoenix pusilla on Colon Cancer Cell Line - Bharadwaj Nikhil; Manimuthu Mani Sankar; Vimal S; Radhakrishnan N (Wolters Kluwer Medknow Publications, 2024)
BackgroundCancer rates continue to climb, owing largely to the world population's aging and growth, as well as economically developing countries, a surge in cancer-causing behavior, particularly smoking. The third or fourth most prevalent type of cancer is colon cancer. Cancer of the large intestine (colon) is one of the primary causes of death from cancer. Colorectal cancer prevention is mostly based on adenomatous disease screening approaches. The cytotoxic and pharmacological properties of Phoenix pusilla are widely documented. As a result, there is little recorded evidence of its cytotoxic activity against colon cancer cells. Therefore, we planned to study the efficacy of a methanolic leaf extract of Phoenix pusilla against in vitro colon cancer cells. AimTo evaluate the anti-cancer effects of the methanolic leaf extract of Phoenix pusilla on colon cancer cell lines. Materials and MethodsIn vitro screening and anti-cancer effects of the methanolic effect of Phoenix pusilla on colon cancer cell lines were assessed by cell viability assays and cell and nuclear morphological studies. For the in vitro cell culture study, different concentrations of Phoenix pusilla leaf extract (0, 25, 50, 75, 100, 150 μg/ml) were used, and IC50 doses were calculated. ResultsThe results of the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay revealed that the fraction of viability cells significantly decreased in treated cells when compared to untreated control groups, was expressed as 100%, and an inhibitory concentration of μg/ml was identified. A phase-contrast microscope was used to observe cell shrinkage and cytoplasmic membrane blebbing. A fluorescent microscope was used to examine the apoptotic nuclei (internally dyed nuclei, shattered nuclei, and condensed chromatin). ConclusionIn conclusion, the present study results showed that the leaf extracts of Phoenix pusilla had a strong cytotoxic effect and induced significant apoptosis in the colon cancer cell lines at a concentration of 75 μg/ml in the 24 h incubation period. More research is needed to investigate the extract's active components as well as the molecular mechanisms underlying its anti-cancer properties.